TEACHING TRANSLATION THROUGH THE INTERACTIVE WEB - Hartono, Rudi (Language Circle: Journal of Language and Literature, 2015)
Translating is a complex and complicated process because it is not only rendering forms of language but also transferring meanings and styles of culture. It needs both a basic knowledge of English and content mastery to produce good products of translation. Teaching translation through the interactive web helped translator students easier, faster, and better translate texts from one language to another one, from example from English into Indonesian language. The problem happened in the Translation Class II taught in the English Department of Semarang State University, Indonesia. The research method used was Action Research that led five steps of research: Identifying the problem, gathering data, interpreting data, acting on evidence and evaluating result (Ferrance, 2000, p.9). In this study I used online tools that facilitated the teaching translation process, such as search engines of translation, translation class sites, tutor and learner blogs, and translation web quests. Practically those online teaching tools were implemented in and out the classroom. The teacher instructed students through the class sites, tutor blog and web quest while the students did their translation practices and tasks using search engines of translation through the learner blogs. The research result showed that teaching translation through the interactive web improved studentsâ translation products from the average score of initial test 73 to the average score of final test 89. It means that this action was significant that increased the progress score up to 1.6.